A structural review of nanoscopic Al1-xTMx phase formation in the TMCln enhanced NaAlH4 system - Pitt, M.; Vullum, P.; Sørby, M.; Emerich, H.; Paskevicius, Mark; Buckley, Craig; Gray, E.; Walmsley, J.; Holmestad, R.; Hauback, B. (Elsevier B.V., 2012)
The twice hydrogen (H) cycled planetary milled (PM) NaAlH4 + xTMCln (transition metal (TM) = Sc, Ti, V, Cr, Mn, Fe, Co, Ni, Cu, Zr, Pd, Pt; 2 < n < 4) and cryo milled (CM) NaAlH4 + xTMCln (TM = Ti, V, Cr, Fe, Ni; 2 < n < 3) systems (x < 0.1) have been studied by high resolution synchrotron X-ray diffraction. Face centred cubic (fcc) A1 crystalline (c-) Al1-xTMx (x < 0.25) solid solutions are evident in PM samples for Sc, Ti, V, Cr, Mn, Zr and Pd while PM samples of Cu, Ni, Pd and Pt display mostly ordered and numerous crystalline Al1-xTMx phases. Very broad reflections in the 2 Å d-spacing region for Cr, Mn, Co, and Pd are identified as partially ordered body centred cubic (bcc) A2 and B2 Al1-xTMx type structures. The amorphous (a-) Al1-xVx phase observed in the H cycled PM NaAlH4 + xVCl3 system ranges in composition from a-Al90V10 (x = 0.02) up to a-Al72V28 (x = 0.1). Across the TM series, the Al1-xTMx particle size ranges as Sc-V 4-25 nm, Cr, Mn, Co <5 nm, Fe 5–15 nm, Ni, Cu <50 nm. A highly ‘compressed’ NaAlH4 phase is observed in the H cycled PM NaAlH4 + 0.1ScCl3 system, with unit cell dimensions of a = 4.9995(2) Å and c = 11.2893(1) Å, compared to the average dimensions of ‘normal’ NaAlH4 across the TM and rare earth (RE) series with a = 5.0228(1) Å and c = 11.3516(1) Å.